Penggunaan Kajian Gastronomi pada Pembelajaran Bahasa Indonesia Teks Observasi di SMK Kompetensi Keahlian Tata Boga - Sutiandari, Ika; Rohman, Saifur; Iskandar, Ifan (Jurnal Paedagogy, 2023)
This study aims to 1) identify media, learning resources, and materials in the culinary arts vocational school that can be integrated with observational texts and gastronomic studies and 2) describe the learning steps in the core learning activities using gastronomic studies in learning observational texts. This research method used qualitative research. Data sources in this study included the syllabus, core competencies, essential competencies, and Indonesian language textbooks class X and Culinary Arts Curriculum 2013. The research used library and observation techniques as data collection techniques. Data analysis in this study was carried out in four stages: data collection, data reduction, data presentation, and drawing conclusions. The results of this study showed that the selection of gastronomic topics on YouTube learning media and resources, online articles, infographics, and the movie could be used as teaching materials for observational texts. It can be integrated with tourism materials, Indonesian cakes, dishes from rice and noodles, leaf folds, and Indonesian soups and soups. Moreover, the learning steps were divided into four Basic Competencies, each with four meetings. The teacher presented articles and videos on KD 3.1 at the first meeting. Then, the teacher showed a YouTube video about gastronomy in the second meeting. 4.1. The teacher presented online articles and infographics at KD. 3.2. In the fourth meeting, the teacher used the movie â€œAruna dan Lidahnyaâ€ to observe the text as an infographic and present culinary products.